Second‐Harmonic Generation in Integrated Photonics on Silicon. Issue 4 (10th October 2017) - Rao, Ashutosh; Fathpour, Sasan
Abstract : This paper presents the recent progress on integrated second‐order nonlinear waveguides on silicon substrates for second‐harmonic generation. In particular, demonstrations of thin‐film lithium niobate, III–V compound semiconductor and dielectric waveguides integrated on silicon substrates are reviewed. For completeness, the fundamentals of the nonlinear optical processes involved are briefly introduced. Methods demonstrated for phase matching, e.g., periodic poling and mode‐shape modulation, in the compact integrated devices are discussed. Finally, an outlook for how integrated photonics may benefit from the progress in this field is provided. Abstract : The success of CMOS electronic integration has spurred an extensive pursuit of integrated photonics on silicon, including numerous recent demonstrations of nonlinear waveguide . This review discusses newly established approaches for realizing second harmonic generation on silicon substrates, using nonlinear waveguides made of a wide range of materials – lithium niobate, III–V compound semiconductors and dielectrics, and silicon itself.